Al Washliyah Ethical Democracy: Patterns, Challenges, and Prospects for Implementation - Setiadi, Ozi; Andriani, Faricha; Nada, Dewi Qodrun (POLITEA, 2025)
Al Washliyah, as an Islamic civil society, has a perspective on an ethical democracy model that utilizes the maqasid of sharia as a medium for ethical democracy. This study will examine Al Washliyah in the context of an ethical democracy model that utilizes the maqasid of sharia as a medium for ethical democracy. Is there a synthesis of ideas for an Islamic-based ethical democracy model that can be developed through the interpretation of Islamic values? How is Al Washliyah's ethical democracy implemented? This study uses a qualitative approach with field research. Data were collected through observation, interviews, and documents. Data were analyzed using triangulation. The theories used are democracy, civil society, and the maqasid of sharia. This study shows that Al Washliyah provides a synthesis of ideas regarding an Islamic-based ethical democracy model through an interpretation of basic Islamic values, especially the concept of maqasid of sharia. This interpretation serves as a foundation for formulating democratic principles that align with Islamic ethics, such as justice, equality, deliberation, and welfare. The implementation of ethical democracy in the context of Al Washliyah has the potential to be carried out through several strategic channels. First, through a broad educational network as a medium for internalizing ethical democracy. Second, through organizational activities that can strengthen the principle of equality. Third, deepening the practice of democracy within organizations as a model for society. Fourth, implementing social control over various public policies. Fifth, engaging in constitutional politics to ensure that political struggles remain within the bounds of Islamic law and ethics.